The Use of Android-Based Comic Media in Science Learning to Improve Student Learning Outcomes - Merry Krysty; Muzzazinah Muzzazinah; Sri Mulyani Sri Mulyani (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
Learning outcomes are key indicators of success in the learning process. This study focuses on the digestive system material and aims to analyze the feasibility and effectiveness of Android-based comic media in improving specific student learning outcomes, namely conceptual understanding and creative thinking skills. The media development followed the 4-D model, which includes four stages: Define (identifying learning needs and objectives), Design (planning the media content and interface), Develop (creating and validating the media with experts), and Disseminate (testing the media's effectiveness in the classroom). Validation by material and media experts showed very good validity scores of 87% and 85.25%, respectively. Effectiveness testing on 30 students at Taman Dewasa Junior High School in Jetis Yogyakarta demonstrated a significant improvement in students' creative thinking skills with an n-gain score of 69%. Compared to conventional learning media, the Android-based comic media offers interactive and visually engaging content that helps students better visualize and understand the digestive system material, creating a more motivating and enjoyable learning environment. However, this study is limited by its relatively small sample size and potential biases in measurement, which should be considered when generalizing the results. Overall, the use of Android-based digital comic media presents an innovative and effective solution to enhance science learning quality.